Analysis Of The Influence Of Domestic Investment, Foreign Investment On The Rate Of Economic Growth In North Sumatra Period (2001-2020) - Anisa Sanas Nalamjra; Nur Aini Simbolon; Sasmi Ebigael Sinaga; Hasyim (Jurnal Manajemen Bisnis Eka Prasetya, 2023)
The phenomenon in this research is that when economic growth experiences an increase, domestic investment, foreign investment and the labor force experience fluctuations over several years. The aim of this research is to analyze the influence of Domestic Investment, Foreign Investment and Labor Force on the Economic Growth of North Sumatra Province. PMDN has an effect on economic growth because domestic investment can provide various benefits, including being able to save foreign exchange and reducing dependence on foreign products. Foreign Investment (PMA) and Domestic Investment (PMDN) is an important source of financing for developing regions and is able to make a significant contribution to development. As a component of capital flows, PMA is considered a relatively stable capital flow compared to other capital flows, for example portfolio investment and foreign debt. The aim of this research is to find out what effect domestic investment and foreign investment have on the rate of economic growth in North Sumatra in the 2001-2020 period.